Stakeholder studies of green buildings: A literature review. (15th August 2022) - Li, Yuanyuan; Li, Min; Sang, Peidong; Chen, Po-Han; Li, Congcong
Abstract: Stakeholders' participation is an essential factor for the promotion of green building (GB) industry and various research studies have been conducted in this area. This paper visually analyzes the literatures on stakeholders' studies of green buildings (GBs) from 2007 to 2021 with the assistance of CiteSpace, HistCite, and VOSviewer, to grasp present research hotspots and explore potential trends. 630 articles were analyzed to identify the most influential regions, institutions, authors, journals, keywords and references in the field. Cluster analysis illustrated that knowledge base focuses more on "evolutionary game", "willingness to pay", "occupant satisfaction", "rehabilitation", "AHP", "safety risk", "green apartments", "stakeholder motivation", "existing residential building" and "life cycle assessment". Current hotspots were detected through citation analysis, including: (1) risks, drivers and obstacles of GB stakeholders, (2) occupants' satisfaction and willingness to pay for GBs, and (3) decision-making process of GB stakeholders. Future research directions are proposed as (1) extending studies to cover all GB stakeholders, (2) more emphasis shift to operation and demolition stages, (3) more investigation on green commercial buildings, and (4) more studies on innovative research methods. The findings in this paper would provide more valuable information for researchers and practitioners interested in this area. Highlights: Research on stakeholder studies of green building projects has experienced a steady growth between 2007 and 2021. Contributing countries, journals, institutions, authors and their relationships were investigated. Cluster analysis, co-words and citation analysis were conducted to explore knowledge base and hotspots in this area. Gaps in previous studies were explored and trends for future research were proposed.